3-Benzyl-4-(4-chlorophenyl)-1H-1,2,4-triazole-5(4H)-thione - Öztürk, S; Akkurt, M; Cansiz, A; Koparir, M; Sekerci, M; Heinemann, FW (Int Union Crystallography, 2004)
In the title molecule, C15H12ClN3S the dihedral angles made by the substituted phenyl and benzyl rings with the triazole ring are 81.39 (10) and 63.59 (10)degrees, respectively. The crystal structure is stabilized by N-H...S, C-H...Cl and C-H...pi interactions.